2021
DOI: 10.1038/s41467-021-23572-4
|View full text |Cite
|
Sign up to set email alerts
|

Smart-watch-programmed green-light-operated percutaneous control of therapeutic transgenes

Abstract: Wearable smart electronic devices, such as smart watches, are generally equipped with green-light-emitting diodes, which are used for photoplethysmography to monitor a panoply of physical health parameters. Here, we present a traceless, green-light-operated, smart-watch-controlled mammalian gene switch (Glow Control), composed of an engineered membrane-tethered green-light-sensitive cobalamin-binding domain of Thermus thermophilus (TtCBD) CarH protein in combination with a synthetic cytosolic TtCBD-transactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Our results demonstrate that endogenous chemiluminescence activates the photoswitchable protein iLID. Such proteins are usually activated through external illumination in optogenetic studies, which limits applications to transparent and nonscattering systems. , Recently, in situ produced bioluminescent light was discovered as an alternative mode of photoactivation. , Here, we demonstrate that the chemiluminescence reaction between luminol and H 2 O 2 is a third way to activate light-responsive proteins. Chemiluminescence has the clear advantage of not needing genetic engineering and being well-established for bioimaging .…”
Section: Discussionmentioning
confidence: 78%
“…Our results demonstrate that endogenous chemiluminescence activates the photoswitchable protein iLID. Such proteins are usually activated through external illumination in optogenetic studies, which limits applications to transparent and nonscattering systems. , Recently, in situ produced bioluminescent light was discovered as an alternative mode of photoactivation. , Here, we demonstrate that the chemiluminescence reaction between luminol and H 2 O 2 is a third way to activate light-responsive proteins. Chemiluminescence has the clear advantage of not needing genetic engineering and being well-established for bioimaging .…”
Section: Discussionmentioning
confidence: 78%
“…The release of CarH from DNA leads to gene activation. TtCBD was also fused with a transactivator to enable green light-inducible transgene expression, such as the human glucagon-like peptide-1 for the treatment of mice with experimental type 2 diabetes ( 190 ). MxCBD and TtCBD have been used to control FGFR1 activity by fusing to the COOH-terminal intracellular domain of FGFR1 and replacing the NH 2 -terminal ligand-binding and transmembrane domains with a myristoylation anchor for PM tethering ( 93 ).…”
Section: Overview Of Photosensory Modulesmentioning
confidence: 99%
“…Using optogenetics, researchers have developed methods to release therapeutic genes using visible light from smartphone as a convenient source to activate the release process, with the goal of making treatment more patient friendly. A recent study by Mansouri et al [78] has shown that the green light from smartwatch is able to remotely control transgene activation and demonstrate the release of human glucagon-like peptide-1 from engineered human cells to treat diabetes. Such an approach is highly promising as the current available smartwatches can project green and red light (corresponding to 540 nm and 690 nm), which is biofriendly and could be used to design various theranostics approaches.…”
Section: Light-based Theranosticsmentioning
confidence: 99%